ANALISIS PERILAKU HERDING INVESTOR PADA CRYPTO LAYER-1 DI PASAR CRYPTOCURRENCY SELAMA PANDEMI COVID-19 - Alzafi, Arizaldi Jofanto; Santi , Fitri (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research examines herding behavior in cryptocurrency market during COVID-19 pandemic. We assume, COVID-19 announcement has a black swan effect on the cryptocurrency market, which results in behavioral anomalies such as herding behavior. This research used Cross-Sectional Absolute Deviation (CSAD) method to determine herding behavior. The sample in this research was 14 cryptocurrency based on the blockchain layer, namely layer-1, and using a purposive sampling technique. Method analysis used is regression analysis. The observation period is from January 2020 to December 2021. This research found that when there was a bullish market condition (up) or bearish market condition (down) there was no indication of herding behavior during the COVID-19 period in the cryptocurrency market. Herding behavior is an interesting topic during crisis periods, when investors share their fears and are vulnerable to large-scale financial panics. This research can increase the understanding of the cryptocurrency market and the financial impact of the COVID-19 pandemic for investors and regulators.